As Parábolas do Reino: um estudo exegético de Lc 13,18-21 - Patuzzo, Izabel (2020)
Jesus spoke about the Kingdom of God by words and actions, during his ministry. Sometimes He did choose reveal the misteries of the Kingdom through Parables. Luke, collecting the data o tradition, inserted the Kingdom’s Parables in the literary context of the travel narrative. Moreover, the grammatical composition of Lk 13:18-21 is interconnected with the previous episode, the healing of the crippled woman (Lk 13:10-17). The interrelation between the narratives of the crippled woman in the synagoge on Sabbath day with the parabolic account, allows establishing a continuity relationship between the liberating actions performed by Jesus with his teaching. According to the Pragmatic linguistics approach in comunicative clue, its highlighted the performative power from those who let themselves to be transformed the parables’s Message seting themselves on the way of discipleship and taking part in Jesus’s actions in order to spread out the Kingdom of God in everywhere. The Parables are an invitation to the disciple-reader get in the dynamics of the man who sows and the woman who makes the bread, because is able to wellcome and identify the signs of the Kingdom in Jesus deeds